Analysis of Sentence Complexity in BBC News “US Bombs Syria Targets After Deadly Drone Attack” - Kadek Surya Adhi Permana; Ida Ayu Mela Tustiawati (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2026)
Writing comprehension is an important aspect for a writer to deliver the message or idea clearly to the readers. The development of English from Old English to Modern English can be seen by looking at the differences between sentences used in any media. In the current development, the internet and technology have developed so much and it has so much influence in many aspects of society. One of the aspects influenced by this development is news media. E-news is one of the examples created by the development of technology. The sentence that appears in E-news sometimes can be complicated. The complexity of sentences can be seen by how the sentences are structured. Sentence and clause types play a big role in identifying the complexity of a sentence. This study aims to identify what are the sentence types and what are the types of subordinate clauses that appear in the data source. The researcher used a qualitative method to analyze the data.